2008
DOI: 10.1002/dys.366
|View full text |Cite
|
Sign up to set email alerts
|

Identifying students feigning dyslexia: preliminary findings and strategies for detection

Abstract: When conducting psychological evaluations, clinicians typically assume that individuals being evaluated are putting forth maximal effort and are not exaggerating or magnifying symptom complaints. Recent research, however, suggests that students undergoing post-secondary-level assessments to document learning difficulties may not always put forth their best effort, and may even be motivated to exaggerate or magnify symptoms. This paper presents evidence indicating that symptom exaggeration in this context is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…Moreover, students motivated to feign ADHD produced lower scores in comparison to those with true disabilities on achievement and processing speed tests designed to determine if accommodations such as extra time would be warranted (Harrison et al, 2007). Similar findings were presented by Harrison, Edwards, and Parker (2008) regarding the ability of students to feign symptoms of reading disorders, with between 70% and 90% of non-disabled ''feigning'' students producing scores on commonly used measures of reading and information processing at levels equal to or lower than those returned by students with genuine reading disabilities. These authors caution clinicians that symptoms of reading disorders are easily fabricated and note that no appropriate symptom validity tests (SVTs) presently exist to assist in identifying students putting forth substandard effort when undergoing an assessment to obtain a disability label.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, students motivated to feign ADHD produced lower scores in comparison to those with true disabilities on achievement and processing speed tests designed to determine if accommodations such as extra time would be warranted (Harrison et al, 2007). Similar findings were presented by Harrison, Edwards, and Parker (2008) regarding the ability of students to feign symptoms of reading disorders, with between 70% and 90% of non-disabled ''feigning'' students producing scores on commonly used measures of reading and information processing at levels equal to or lower than those returned by students with genuine reading disabilities. These authors caution clinicians that symptoms of reading disorders are easily fabricated and note that no appropriate symptom validity tests (SVTs) presently exist to assist in identifying students putting forth substandard effort when undergoing an assessment to obtain a disability label.…”
supporting
confidence: 70%
“…Overall, it seems clear that SVTs are required in psychoeducational assessments of LD and ADHD, as both conditions are vulnerable to feigning (Frazier, Frazier, Busch, Kerwood, & Demaree, 2008;Harrison et al, 2007Harrison et al, , 2008. Further, this study confirms that a sizeable minority of students undertaking these evaluations are producing scores that are non-credible, which may lead to inaccurate interpretation of their data as reflecting a disability.…”
Section: Limitations and Directions For Future Researchsupporting
confidence: 54%
“…Therefore tests are not infallible and when used on a highly selected population of students may not give true results or may be more prone to manipulation by the candidate. The work by Harrison et al (2008) has shown promise in the production of an additional test that highlights students feigning a SpLD to obtain a false diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Studies demonstrated that a considerable amount of undergraduate students do engage in some kind of academic cheating during their studies (Pincus and Schmelkin 2003;Hughes and McCabe 2006). According to Harrison et al (2008), there is an increase in the number of students who present themselves to specialists at the post-secondary-level because of symptoms of ADHD. Second, it is likely that stimulant medications are prescribed to adults who successfully feign ADHD.…”
Section: Introductionmentioning
confidence: 98%